Revitalizing identity in language: a Kristevan psychoanalysis of suddenly last summer - Hezaveh, Leila Rezaei; Nurul Farhana Low Abdullah,; Md Salleh Yaapar, (Penerbit UKM, 2014)
Tennessee Williams‟s plays have frequently been criticized for overt use of poetic language and his constant focus on poetic devices such as alliteration and metaphor, as well as tropes like violence and feminine madness. A psychoanalytic study of his famous drama Suddenly Last Summer (1958) will enable us to explore the qualities of unresolved psychological complexes in the characters and also in the author himself, as the play is believed to draw strongly upon the playwright‟s own biography. Towards this end, an intertextual interpretation serves to reflect upon the semiotic disposition of author and characters, which figures out a paradigm of the “transcendental ego” (Moi, 1986, p. 28). This analysis therefore aims at projecting the unconscious of the characters and the author through language, while examining how language can represent characters‟ identities and their hidden complexes through fragmentation of their identities. Through the analysis it will be shown how the interpretation of poetic language uncovers the unconscious via the effects and affects of devices such as metaphor, metonymy, replacement and condensation. Using a Kristevan interpretation of poetic language and its revelation of the semiotic, this paper therefore attempts to show that violence presented in the text is rooted in the fragmented identities of the characters and their creator and ultimately, it suggests the potential to recover one‟s identity through poetic language. It may thus offer some clues to puzzling issues that have been misunderstood with regard to the recurrent poetic language and images in Suddenly Last Summer.